Satellite teleconferencing in the Caribbean - Sankar, Hollis Carlyle
This article discusses the need for, and the development, use, and future trends of The University of the West Indies Distance Teaching Experiment (UWIDITE), which utilizes telephone and communications satellite technology teleconferencing to extend educational opportunities to the peoples of the Caribbean
doi: 10.1080/09523988508548825
Keywords: UWIDITE